PENGARUH TRANSPARANSI, EFISIENSI ANGGARAN, KINERJA KESELAMATAN TRANSPORTASI TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH : STUDI TERMINAL TIPE A ALBN SUI AMBAWANG - Aulia Izzaky, Diva; Karpriana, Angga Permadi (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2025)
This study aims to analyze the effect of transparency, budget efficiency, and transportation safety performance on the accountability of government agency performance at Terminal Type A ALBN Sui Ambawang, West Kalimantan. The background of this research is based on the importance of accountability as an indicator of good governance, especially in the context of strategic border terminal management. This research uses a quantitative approach with a survey method to 83 respondents who are operational and managerial employees of the terminal, using a Likert scale questionnaire instrument. Data analysis was performed with multiple linear regression using SPSS 26. The results showed that simultaneously, transparency, budget efficiency, and transportation safety performance had a significant effect on the performance accountability of government agencies. However, partially, only budget efficiency and transportation safety performance have a significant effect, while transparency has no significant effect. Budget efficiency has the greatest influence on accountability, followed by safety performance. This research provides theoretical contributions to the public sector accountability literature and practical implications for the management of border terminals, especially in terms of strengthening the efficiency of budget use and improving transportation safety standards as part of the accountability of government institutions.